ANALISIS KADAR KESADAHAN TOTAL PADA AIR SUMUR DI PADUKUHAN BANDUNG PLAYEN GUNUNG KIDUL YOGYAKARTA - Dian Wuri Astuti; Siti Fatimah; Sawlenitami Anie (Analit : Analytical and Environmental Chemistry, 2016)
Water is a natural resource that is indispensable for the livelihood of many people. Good water is water that meet the requirements of physics, microbiology, chemical. Chemically there is no water in the form of chemical substance Arsenic, Iron, chloride, and hardness in the form CaCO3. Hardness is a condition with excessive limecontent in the water. Hardness with high concentrations consumed in a long period of time can be detrimental to health. Padukuhan Bandung is one of the padukuhan that are in Padukuhan Bandung Kecamatan Playen Kabupaten Gunung Kidul who use wells for drinking and house hold needs. Some factor that interfere with residents’ wells are the white deposits on the water that cause public health problems, and the frequent occurrence of blockage of the channel pipe is used. This kind of research method is descriptive. Result on this study, obtained 3.58% af water wells that do not meet the requirements of the 28 samples examineted. Conclusion 3.58%  watter wells not meet the requirements.